(untitled) (New Hope, Pennsylvania, 1998)
The Handbook of Corporate Debt Instrument provides a practical overview of the wide range of corporate debt products available for enhancing returns over government securities. Contributions from dozens of highly respected analysts and portfolio managers give financial professionals and individual investors alike an incredible opportunity to learn about and use corporate debt products to their fullest.
Keywords: Financial instruments,Investments